A importância da atuação de Indígenas Intérpretes de Libras em um contexto cultural Indígena: Exposição “Xingu: Contatos” - Santos-Pankararu, Luciana Maria (Universidade Federal de São Carlos, 2024)
This paper, by presenting and discussing the work of indigenous interpreters of Libras in contexts in which indigenous ethnic-cultural issues are addressed, advocates the work of these professionals as fundamental to guaranteeing accessibility for deaf people to the Brazilian indigenous socio-cultural context, understanding the linguistic, social and cultural singularities of both communities (deaf and indigenous). Thus, based on the analysis of the work of three indigenous professionals in the exhibition “Xingu: Contatos”, held by the Moreira Salles Institute in São Paulo between 2022 and 2023, we highlight the importance of the work of these Libras interpreters, given the particularities of indigenous cultural diversity and the pressing issue of indigenous representation also in the field of training/work of professional interpreters of Portuguese and Libras. For the discussion, videos of these professionals' work were analyzed, characterizing the research as documentary, of a qualitative nature. The research presented a brief overview of reflections, which allows us to encourage the training of indigenous people as translators and interpreters of Libras, seeking to foster interdisciplinary discussions that address the ethical, social, linguistic and cultural aspects in deaf and indigenous contexts and, more specifically, in the field of training in the area of translation and interpretation of Libras/Portuguese Language.
The importance of the performance of Indigenous Libras Interpreters in an Indigenous cultural context: “Xingu: Contacts” Exhibition
Keywords: Formação de intérpretes de Libras; Indígenas tradutores e intérpretes de Libras; Tradução/interpretação para a Libras na esfera cultural; Exposição Xingu; Training of Libras interpreters; Indigenous Libras translators and interpreters; Translation/interpretation for Libras in the cultural sphere; Xingu exhibition; OUTROS